SUSTAINABILITY OF THE BANKING SYSTEM AND PRINCIPLES OF ITS ASSESSMENT - Orzudzhon S. Makhmadov (Вестник Российского экономического университета имени Г. В. Плеханова)
Ensuring sustainability of the banking system is one of the most important problems of public development. Its decision is necessary both in the period of economic growth and economic depression and rising economic and political risks. The author investigates differences between the terms ‘sustainability’, ‘stability’ and ‘reliability’ in Russian and overseas sources and provides opinions of some authors about these differences. Apart from that he identifies signs of sustainability of the banking system in economy of various countries.